Harem Years : The Memoirs of an Egyptian Feminist, 1879-1924 - Shaʻrāwī, Hudá, 1879-1947 (Book collections on Project MUSE., 1987)
Married at 13 against her wishes, Shaarawi grew up to be an early leader of Egypt's feminist movement.